Intraocular Foreign Body: Striving the Optimal Visual Outcome - Muhammad Firmansjah; Nandang Sudrajat; Ima Yustiarini; Ady Dwi Prakosa; Sauli Ari Widjaja; Wimbo Sasono (Vision Science and Eye Health Journal, 2023)
Introduction: Intraocular foreign bodies (IOFBs) are defined as intraocularly retained, unintentional projectiles that require urgent diagnosis and treatment to prevent blindness or globe loss. Case Presentation: We report a case of IOFB due to occupational accidents. In this case, there were delays in extraction considering the health facilities and conditions related to COVID-19 infection. Initially, the patient underwent closure of the entrance wound, which was performed within the first 24 hours post-trauma. However, although there was no endophthalmitis, visual acuity at the end of the observation still showed an unexpected outcome. The patient was followed up for three months after IOFBs extraction. The timing of IOFBs removal depends on several factors, including the patient’s overall health status, the nature of the injury, and the composition of the IOFBs. The postoperative examinations focus on complications such as endophthalmitis, postoperative retinal detachment, proliferative vitreoretinopathy (PVR), and sympathetic ophthalmia. The numerical values can then be used to predict the expected visual acuity using the ocular trauma score system. Conclusions: Many factors could affect the outcome quality of visual acuity. Primary wound closure, foreign body extraction, and anatomic reconstruction of the holistic ocular should be performed as soon as possible. Delay in definitive treatment was thought to affect worsening prognosis due to tissue proliferation and the tendency for severe complications, including endophthalmitis.